Defeatist Beliefs and Schizotypy in Adolescents and Emerging Adults - Devin Massaro; Gianna Capodilupo; Sarah Ehrlich; George Nitzburg; Thomas James Dinzeo (Utan Kayu Publishing, 2024)
Defeatist beliefs involved overgeneralized negative beliefs regarding the ability to successfully perform tasks and accomplish goals. These cognitive errors have been shown to affect one’s ability to accurately assess and react in social situations and serve as hallmarks of many mood disorders. These negative beliefs also exist at high rates in adults with schizophrenia spectrum diagnoses. There is evidence for these beliefs existing during prodromal periods in young adults at-risk for psychosis, especially if they exhibit motivational or interpersonal difficulties (negative symptoms). However, there is little known about when these beliefs first emerge and whether they predate clinical disorder during earlier life stages where only subclinical presentations of risk (schizotypy) may be present. To address this research gap and help to inform cognitive-behavioral interventions targeting defeatist belief structures, we investigated the relations between defeatist beliefs and schizotypy in a sample of adolescents and emerging adults. Participants were 86 high school students (ages 14-17) and 270 college students (ages 18-22). Participants completed a 30-minute, self-report survey on defeatist beliefs and schizotypy. Our analyses found little difference in mean or standard deviation in defeatist beliefs or schizotypy between our two samples, with a robust positive association (r=0.46) when the samples where aggregated. These findings suggests that defeatist beliefs correspond with subclinical risk more-or-less on a continuum during this wider period of life potentially helping to understand variability in symptom severity. Future research is needed to clarify the nature of this relationship and to inform future interventions. Our finding suggests that cognitive behavioral approaches, which are well suited to target and modify defeatist beliefs, could serve a preventative role in the risk for future psychosis in at-risk adolescents and emerging adults.